2003
DOI: 10.1007/s00415-003-0192-3
|View full text |Cite
|
Sign up to set email alerts
|

High field MRI correlates of myelin content and axonal density in multiple sclerosis

Abstract: Different MRI techniques are used to investigate multiple sclerosis (MS) in vivo. The pathological specificity of these techniques is poorly understood, in particular their relationship to demyelination and axonal loss. The aim of this study was to evaluate the pathological substrate of high field MRI in post-mortem (PM) spinal cord (SC) of patients with MS. MRI was performed in PMSCs of four MS patients and a healthy subject on a 7 Tesla machine. Quantitative MRI maps (PD; T2; T1; magnetization transfer ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
206
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(225 citation statements)
references
References 38 publications
16
206
1
2
Order By: Relevance
“…Recent studies using animal models further demonstrated that a loss of axons is repre- sented by a decreased longitudinal diffusivity and a normal transverse diffusivity, whereas myelin breakdown is represented by an increased transverse diffusivity and a normal longitudinal diffusivity (33)(34)(35)(36)). Another postmortem study demonstrated a strong correlation of the axonal density and loss of myelin with the diffusion anisotropy and a weaker correlation with the MD (48). As also proposed by Agosta et al, astrocytic proliferation, cell debris, fibrillary gliosis, and inflammatory infiltrates can result in a normalization of the MD values and can, therefore, prevent the MD differences to be statistically significant, as observed in our study (17,22,49).…”
Section: Discussionsupporting
confidence: 80%
“…Recent studies using animal models further demonstrated that a loss of axons is repre- sented by a decreased longitudinal diffusivity and a normal transverse diffusivity, whereas myelin breakdown is represented by an increased transverse diffusivity and a normal longitudinal diffusivity (33)(34)(35)(36)). Another postmortem study demonstrated a strong correlation of the axonal density and loss of myelin with the diffusion anisotropy and a weaker correlation with the MD (48). As also proposed by Agosta et al, astrocytic proliferation, cell debris, fibrillary gliosis, and inflammatory infiltrates can result in a normalization of the MD values and can, therefore, prevent the MD differences to be statistically significant, as observed in our study (17,22,49).…”
Section: Discussionsupporting
confidence: 80%
“…Currently available quantitative MRI techniques have been validated using standard histology (Mottershead et al, 2003;Schmierer et al, 2003Schmierer et al, , 2004Schmierer et al, , 2007aFisniku et al, 2009). However, a rigorously quantitative validation of magnetic resonance pathologic metrics has been relatively limited in part due to the difficulty to co-register quantitative histology findings with MRI.…”
Section: Discussionmentioning
confidence: 99%
“…The local tissue microstructure is evaluated with several indices, inclu ding mean diffusivity and fractional anisotropy, which corre late with myelin content, tissue integrity and axonal loss. 54 Proton magnetic resonance spectroscopy ( 1 H MRS) can add information on the biochemical nature of MS related abnormalities, by quantifying several CNS metabo lites. 55 T2 hypointense areas and reduced T2* relaxation time (or its reciprocal R2*) are thought to be associated with iron deposition, which is believed to be a sign of neurodegeneration in patients with MS. 56 Application of these techniques to characterize the extent and distribution of MS related damage within focal lesions or in normal appearing white and grey matter has shown that tissue disruption in patients with progressive disease is more severe and more widely distributed than in patients with relapsing forms of MS. 57 Additionally, struc tural CNS damage has been shown to progress at different rates across the major clinical pheno types of MS.…”
Section: Focal Lesionsmentioning
confidence: 99%